Fourteen days struggling to deal with COVID-19 using Su Jok Therapy: A case report - Intansari Nurjannah (Journal of Community Empowerment for Health, 2022)
The resources to deal with COVID-19 are lessening, while health professionals are increasingly vulnerable in helping people with COVID-19. The close contact between health professionals and patients with COVID-19 increases the already high risk for transmission. It is time to find another form of therapy to help people with COVID-19 which is effective, inexpensive, easy and safe that can be done both for the well-being of patients and health professionals. In 2020, a male patient who was in his middle age, was seeking treatment from health professionals by sending messages through WhatsApp since he tested positive for COVID-19 the day before. We assessed him and found that he had complaints of fever, shivering and difficulty in breathing. We immediately replied with Su Jok protocol therapy and asked him to do the treatment by himself. After 27 minutes, there was no difficulty in breathing anymore. Since then, we kept monitoring his condition closely and provided instructions every day to treat each symptom. The most prominent symptoms associated with COVID-19 were shivering, difficulty in breathing, fever, excess mucus and pain in the lungs. Psychological symptoms also appeared and Su Jok was applied to treat his emotional problems. Symptoms attacked him less frequently and with less severity day by day. His swab test showed negative result after two weeks. In this case study, Su Jok therapy helped a patient in quarantine to deal with the physiological and psychological symptoms of COVID-19. Su Jok therapy can also help to prevent transmission of COVID-19 to health professionals, since they still can help patients from a distance with telehealth.